Children's, parents' and professional stakeholders' views on power concerning the regulation of online advertising of unhealthy food to young people in the UK: A qualitative study. - Lauren Carters-White; Shona Hilton; Kathryn Skivington; Stephanie Chambers (PLoS ONE)
Examinations of corporate power have demonstrated the practices and activities Unhealthy Commodity Industries (UCIs) employ to exert their power and influence on the public and health policy. The High in Fat Sugar and Salt (HFSS) product industry have exploited the online environment to market their products to young people. Regulating UCIs' marketing can limit the power of those industries and is argued to be one of the most appropriate policy responses to such marketing. However, there is minimal consideration of how stakeholders view regulation of online advertising of HFSS products to young people. This UK-focused study addressed this through a secondary analysis of focus groups with young people (n = 15), the primary analysis of focus groups with parents (n = 8), and interviews with professional stakeholders (n = 11). The findings indicated that participants' views on the regulation of online advertising of HFSS products were informed by how professional stakeholders exerted instrumental, structural and discursive power. Participants cited regulation as a means to re-negotiate problematic power dynamics to increase young people's and parents' autonomy over young people's diets, yet concern remained as to the impact regulation may have on individual autonomy. To garner increased public support for such regulatory policies, it may be beneficial for advocates to emphasise the empowering elements of those regulatory policies. Advocacy actors may wish to shift their framing of regulation from one that focuses on restricting industry practices, to one that centres on empowering individuals.